Coexistence of apical hypertrophic cardiomyopathy and endomyocardial fibrosis with calcification: diagnosis using multimodality imaging. (28th July 2016) - Muthukumar, Lakshmi; Jan, M. Fuad; Whitnah, Joseph; Tajik, A. Jamil
Abstract: A 48‐year‐old man from West Africa was evaluated for dyspnea. Echocardiography showed an echolucent mass at the left ventricular apex surrounded by a dense ridge of tissue, suggesting endomyocardial fibrosis (EMF). Doppler echocardiography showed restrictive hemodynamics and intramyocardial coronary blood flow at the hypertrophied apex, suggesting apical hypertrophic cardiomyopathy (ApHCM) with calcified thrombus. Cardiac magnetic resonance imaging showed a thickened myocardium with apical cavity obliteration and endomyocardial calcification, and gadolinium contrast demonstrated marked bright subendocardial and diffuse patchy intramyocardial hyperenhancement in the hypertrophied apical wall segment, confirming coexistence of EMF and ApHCM. Workup for known disorders of calcification was negative.